2021
DOI: 10.1101/2021.02.03.429549
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Structural variability and concerted motions of the T cell receptor – CD3 complex

Abstract: We investigate the structural and orientational variability of the membrane-embedded T cell receptor (TCR) - CD3 complex in extensive atomistic molecular dynamics simulations based on the recent cryo-EM structure determined by Dong et al., Nature 573:546 (2019). We find that the TCR extracellular (EC) domain is highly variable in its orientation by attaining tilt angles relative to the membrane normal that range from 15° to 55°. The tilt angle of the TCR EC domain is both coupled to a rotation of the domain an… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
11
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
2
1

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(14 citation statements)
references
References 48 publications
3
11
0
Order By: Relevance
“…In the TCR-only system, in which the TCR EC folded over the CD3 co-receptors (Figure 1A), the TCR adopted predominantly bent conformations (smaller angles), with a peak in the distribution at 104°. Such bending was observed in previous simulations of the same starting structure (Pandey et al, 2021). In contrast, the TCRs in the TCR-pMHC system, for which the many interactions with CD3 were broken, tended to adopt an extended and open conformation (larger angles, with the peak of the distribution at 150°) where the TCR EC tilted away from the CD3 EC domains (Figure 4 and Figure 1B).…”
Section: Resultssupporting
confidence: 81%
See 1 more Smart Citation
“…In the TCR-only system, in which the TCR EC folded over the CD3 co-receptors (Figure 1A), the TCR adopted predominantly bent conformations (smaller angles), with a peak in the distribution at 104°. Such bending was observed in previous simulations of the same starting structure (Pandey et al, 2021). In contrast, the TCRs in the TCR-pMHC system, for which the many interactions with CD3 were broken, tended to adopt an extended and open conformation (larger angles, with the peak of the distribution at 150°) where the TCR EC tilted away from the CD3 EC domains (Figure 4 and Figure 1B).…”
Section: Resultssupporting
confidence: 81%
“…This observation raised the question of whether the angle between the TCR EC and transmembrane domain (TM) is dynamic. Molecular dynamics studies based on the complete TCR structure in a membrane demonstrated that the TCR is indeed flexible and that the TCR headgroup can adopt a range of different conformations (Prakaash et al, 2021; Pandey et al, 2021).…”
Section: Introductionmentioning
confidence: 99%
“… The shading of the contact disks indicates the contact probability, that is the fraction of simulation structures in which the contact is present. The contact analysis is based on 120 × 50 = 6000 structures extracted at intervals of 10 ns from the second halves of the 120 μs-long trajectories, which reflect an equilibrated ensemble of simulation conformations (see Materials and methods) and are available at the Edmond Open Research Data Repository ( Pandey and Weikl, 2021 ). For clarity, only contacts with a contact probability larger than 0.5% are represented.…”
Section: Resultsmentioning
confidence: 99%
“…The contacts, contact numbers, and angles presented in Figures 2 and 3 are calculated from these 6000 structures. The 6000 structures are available at the Edmond Open Research Data Repository at https://dx.doi.org/10.17617/3.5m ( Pandey and Weikl, 2021 ).…”
Section: Methodsmentioning
confidence: 99%
“…Useful and appropriate tools for generating conformational ensembles of biomolecules are molecular dynamics (MD) simulations. However, despite steady developments in this field [ [23] , [24] , [25] ], all-atom MD simulations of multi-domain and partially disordered proteins are still challenging – not only because of the large sizes of such proteins but also because of the long time scales on which large conformational fluctuations occur. Coarse-grained molecular simulations, on the other hand, provide means to efficiently sample conformational ensembles of large, multi-domain and dynamic proteins and their complexes [ 4 , 20 , 26 ].…”
Section: Introductionmentioning
confidence: 99%